Adapting the Australian Canon and Decolonizing the Tertiary Classroom: Settler Students Respond to Leah Purcell's The Drover's Wife. (28th December 2021) - Hall, Demelza; Storey, Kate; Benney, Laura; Bourke, Marlee
Abstract: The 'Drover's Wife Reading Group' was a collaborative teacher–student project piloted between 2018 and 2020 at Federation University Australia with the intention to create spaces for decolonization, particularly settler (un)learning, beyond the limits of the tertiary English classroom. Drawing upon aspects of reader–response theory, the project began as a small constructivist study in that it sought, initially, to gauge the different responses undergraduate settler students had to a work of Indigenous Australian literary adaptation. However, the transformative nature of the text being engaged with – Leah Purcell's play, The Drover's Wife (2016), a literary work which has been widely recognized for the critical literacy it promotes – coupled with the sophistication of the participants' various responses to it, quickly saw the project shift to one of intense collaboration, with the students involved becoming partners in shaping the project's outcomes.